Development of Foreign Language Teaching Material Based on Higher Order Thinking Skills (HOTS) to Increase Students’ Literacy Skills - Muh. Anwar (Makassar State University, 2021)
Abstract. The purpose of this study is to develop an foreign language teaching material based on Higher Order Thinking Skills (HOTS) and to investigate the impacts of the implementation of the teaching material in increasing students’ literacy skill. This study used research and development approach by adopting ADDIE model which consisted of 5 steps (Analyze-Design-Develop-Implement-Evaluate). The participants of the study were 25 students who took General Writing and Reading course in the English Literature study program in the fifth semester. An assent form was given to all the participants. Data were collected by using study test results, scale and interview. The data of the study were 1) the results of validation test from five expert validators regarding the teaching material being developed, 2) the results of students’ study test comprised of writing and reading tests, and 3) qualitative data regarding students’ responses to the teaching material being developed. The data were analyzed using descriptive statistics and inferential statistics. Descriptive statistics were used to make categorization of pre-test and post-test scores, while inferential statistics were used to analyze the paired sample t-test to know if there was a significant difference between pre-test and post-test. The results of the study showed that the implementation of HOTS-based teaching material being developed had positive impacts significantly on the improvement of students’ literacy skill, which were in this regard the results of learning General Writing and Reading course. Students responded favorably to the implementation of the teaching material because it allowed them to think critically and creatively. Keywords: Teaching material, Foreign language teaching, Higher Order Thinking Skills (HOTS), Studens’ literacy skill.